Överföring av radiocesium till potatis vid olika nedfallstidpunkter - Stenmark, Marielle (2008)
Agricultural land could be polluted by radioactive substances after a fallout. We would then need information about the level of contamination to decide whether the crops could be utilized as food under these circumstances. In an experiment carried out during the 1990ies the retention of 134Cs in potato haulm and the transfer to the tubers were studied. The experiment was carried out during three consecutive years. The plants were cultivated in pots under field conditions and the artificial deposition was sprayed directly onto the potato haulm at different times during the growing season. The results showed that the time of fallout and the developmental stage of the crop controlled the 134Cs content in the harvest-mature potato tubers. The highest content was detected in the case of a fallout in the middle of the growing season. In the case of an early fallout, the change in 134Cs content during the growing season decreased with time. After a late fallout the content tended to increase with time which was supposedly due to an active transport during the later stages of crop development. Assuming a fallout corresponding to 10 kBq the 134Cs content in the harvest-mature potato tubers would be above the permitted threshold value after a radioactive fallout taking place in the middle of the growing season. Actions to decrease the Cs content below the threshold value may include potassium fertilisation, an early harvest or cutting of the potato haulm.